2013
DOI: 10.1007/s10533-013-9832-6
|View full text |Cite
|
Sign up to set email alerts
|

Afforestation with Norway spruce on a subalpine pasture alters carbon dynamics but only moderately affects soil carbon storage

Abstract: There is a strong trend toward reforestation of abandoned grasslands in alpine regions which may impact the carbon balance of alpine ecosystems. Here, we studied the effects of afforestation with Norway spruce (Picea abies L.) on an extensively grazed subalpine pasture in Switzerland on soil organic carbon (SOC) cycling and storage. Along a 120-year long chronosequence with spruce stands of 25, 30, 40, 45, and [120 years and adjacent pastures, we measured tree biomass, SOC stocks down to the bedrock, natural 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
45
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 49 publications
21
45
1
Order By: Relevance
“…The significantly higher winter CO 2 fluxes in the grassland compared to the forest (Fig. 8) are consistent with the observation of decreasing summer soil respiration rates during afforestation of a subalpine pasture (Hiltbrunner et al, 2013). In their study the lower rates in the forest were explained with a smaller root turnover, a lower litter quality and a less favorable microclimate in the forest than in the adjacent grassland.…”
Section: Spatial Variability Of Ghg Fluxes Across Different Land Usessupporting
confidence: 87%
“…The significantly higher winter CO 2 fluxes in the grassland compared to the forest (Fig. 8) are consistent with the observation of decreasing summer soil respiration rates during afforestation of a subalpine pasture (Hiltbrunner et al, 2013). In their study the lower rates in the forest were explained with a smaller root turnover, a lower litter quality and a less favorable microclimate in the forest than in the adjacent grassland.…”
Section: Spatial Variability Of Ghg Fluxes Across Different Land Usessupporting
confidence: 87%
“…Other studies also reported higher contents of organic C in forest than in grasslands (Guo et al 2007;Guidi et al 2014). As a consequence of reduced soil temperature and moisture following forest succession (Hiltbrunner et al 2013), the decomposition of organic matter is slowed down, leading to a decreased incorporation of C into soil aggregates (Gregorich et al 2006). As discussed by Guidi et al (2014), such an increase of C content in the soil is a typical positive effect of transitional phases between grasslands and forest.…”
Section: Cover Of R Ferrugineum Is Related To the Distribution Of Fimentioning
confidence: 93%
“…While afforestation of moorland increased Rs, afforestation of grassland significantly reduced Rs. A number of previous studies reported reductions in Rs upon afforestation of pasture and cropland ScottDenton et al, 2006;Hiltbrunner et al, 2012Hiltbrunner et al, , 2013Wang et al, 2013;Zhang et al, 2013) that was attributed to low C inputs from tree to belowground communities. This observation is consistent with a previous report of considerably lower primary production and soil respiration in forest compared with grassland at the field scale (Schulze et al, 2010).…”
Section: Land Use Impact On Soil Respiration and Microbial Community mentioning
confidence: 97%